PENINGKATAN PARTISIPASI BELAJAR DALAM PEMBELAJARAN ORGAN GERAK HEWAN DAN MANUSIA MENGGUNAKAN MODEL KOOPERATIF PADA PESERTA DIDIK KELAS VB SDIT AL-MUMTAZ PONTIANAK - Elisa, Elisa; Halidjah, Siti; Kresnadi, Hery (Universitas Tanjungpura, 2024)
The background of the thesis is the low level of learning participation and student learning outcomes at SDIT Al-Mumtaz. The aims are: to describe the learning outcomes and to describe the increase in student participation in learning science in the material Organs of Movement of Animals and Humans by using a cooperative learning model for students. This thesis is a class action thesis. The subject of this thesis is all participants, totaling 32 students. The data collection method uses observation to observe student activities in science learning Material Organs and Movement of Animals and Humans through observation and pretest, observation to determine the level of student participation, while the pretest is used to obtain data on the ability of learning outcomes in cycles I and II. Data analysis researchers used descriptive statistics by looking for the average value and percentage of learning outcomes and student participation from cycle I and cycle II. Based on the results of data analysis, it can be explained that the average value of student learning outcomes has increased and has reached the competency standards of the KKM set by the school. The teacher's actions in carrying out the stages in learning with the cooperative learning model greatly affect the learning participation of students. At the end of the cycle, all participation indicators experienced a significant increase.